Linguistics and education
Linguistics and Education encourages submissions that apply theory and method from all areas of linguistics to the study of education. Areas of linguistic study include, but are not limited to: text/corpus linguistics, sociolinguistics, functional grammar, discourse analysis, critical discourse analysis, conversational analysis, linguistic anthropology/ethnography, language acquisition, language socialization, narrative studies, gesture/ sign /visual forms of communication, cognitive linguistics, literacy studies, language policy, and language ideology.